Modifiable factors associated with pediatric asthma readmissions: a multi-center linked cohort study. (3rd April 2023) - Chen, Katherine YH; Chu, Wanyu; Jones, Renee; Vuillermin, Peter; Fuller, David; Tran, David; Sanci, Lena; Shanthikumar, Shivanthan; Carlin, John; Hiscock, Harriet
Abstract: Objectives: To (a) identify rates of hospital readmission and emergency department (ED) re-presentation for asthma within a 12-month period, (b) estimate the effects of modifiable hospital, general practitioner (GP) and home environmental factors on hospital readmission, ED re-presentations and rescue oral corticosteroid use. Methods: We recruited 767 children aged 3–18 years who were admitted to 3 hospitals in Victoria, Australia between 2017 and 2018 with a validated diagnosis of asthma on chart review. Primary outcome was hospital readmission with asthma within 12 months of index admission. Secondary outcomes were ED re-presentation for asthma and rescue oral corticosteroid use. All outcomes were identified through linked administrative datasets. Their caregivers and 277 nominated GPs completed study surveys regarding the home environment and their usual asthma management practices respectively. Results: Within 12 months of an index admission for asthma 263 (34.3%) participants were readmitted to a hospital for asthma, with participants between the ages of 3–5 years accounting for 69.2% of those readmitted. The estimated effect of GP reported guideline discordant care on the odds of readmission was OR 1.57, 95% CI 1.00–2.47, p  = 0.05. None of the hospital or home environmental factors appeared to be associated with hospital readmissions. Conclusions: Hospital readmissions among Australian children with asthma are increasing, and linked datasets are important for objectively identifying the health services burden of asthma. They also confirm the important role of the GP in the management of pediatric asthma.